1996
DOI: 10.1901/jaba.1996.29-345
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Technology for the Use of Operant Extinction in Clinical Settings: An Examination of Basic and Applied Research

Abstract: Extinction of operant behavior, which involves terminating the reinforcement contingency that maintains a response, is important to the development, generalization, and reduction of behavior in clinical settings. We review basic and applied research findings on variables that influence the direct and indirect effects of extinction and discuss the potential value of a general technology for the use of extinction. We suggest that current research findings are not sufficient for the development of a comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
124
1
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(130 citation statements)
references
References 238 publications
(320 reference statements)
2
124
1
3
Order By: Relevance
“…For example, Lerman and Iwata (1996) noted that therapists often implement extinction merely by changing their behavior and that, under such an arrangement, there is a shift from baseline to treatment contingencies while many of the stimuli associated with both remain constant. The results obtained in this study indicate that an interesting avenue for future research would be to determine whether faster treatment effects are obtained if baseline and treatment sessions are correlated with highly salient S D s.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lerman and Iwata (1996) noted that therapists often implement extinction merely by changing their behavior and that, under such an arrangement, there is a shift from baseline to treatment contingencies while many of the stimuli associated with both remain constant. The results obtained in this study indicate that an interesting avenue for future research would be to determine whether faster treatment effects are obtained if baseline and treatment sessions are correlated with highly salient S D s.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have evaluated the efficacy of extinction procedures in the reduction of aberrant behavior (Lerman & Iwata, 1996). The use of extinction has been associated with a number of behavioral patterns including a temporary increase in response frequency (Iwata, Pace, Kalsher, Cowdery, & Cataldo, 1990) and extinction-induced aggression (Goh & Iwata, 1994).…”
mentioning
confidence: 99%
“…Studies have noted several problematic characteristics when behaviors are exposed to an extinction procedure including the extinction burst; indirect effects such as aggression, emotional responding, as well as resurgence of previously reinforced behavior; and spontaneous recovery of the behavior undergoing extinction (Lerman & Iwata, 1996). It has also been suggested that the negative side effects induced by escape extinction may deter caregivers from attempting to implement or wanting to implement such a procedure (Penrod et al, 2010).…”
Section: Alternative Treatmentsmentioning
confidence: 99%